The Effectiveness of Opinion-Gap Activity to Improve Writing Discussion Text - Monitha Geraldine (Jurnal Ilmiah Spectral, 2017)
This research objective was to find out whether teaching writing discussion text through opinion-gap activity based on Task-Based Language Teaching (TBLT) approach was effective or not. To accomplish the purpose of this study, a quasi experimental design was utilized. The measurement technique was employed in this research. The data collection instrument was written test. The t-test formula was applied to analyze the quantitative data obtained through written test, while an analytic scoring rubric was developed to assess the students’ writing in discussion text. The results of data analysis through statistical procedure of t-test confirmed the superiority of the experimental group to the control group, and opinion-gap activity helped the students to improve their writing discussion text.